A study on the effect of UV crosslinking time on the degradation of 3D core-shell microspheres - Toh, E-Lynn (Nanyang Technological University, 2020)
Development of natural protein-based fibrous scaffolds like gelatin methacryloyl (GelMA) with modifiable physical properties and biocompatibility is highly desirable to construct three-dimensional (3D), fully cellularized scffolds for wound healing[1]. The goal of this project is to study how GelMA with different degrees of substitution are able to form coreshell spheroids using co-axial electrospraying. The synthesis of GelMA spheroids was done according to a standard protocol, with varying degrees of substitution (DS). Mechanical properties of the GelMA like its viscosity and storage modulus were studied through the use of a rheometer for the different DS, while the study of porosity was done using SEM. The effect of different degrees of substitution of methacrylic anhydride (MAA) with the amine groups present in the gelatin powder at 50% and 96% were studied. Results revealed that DS96 GelMA had better mechanical properties, lower viscosity and a bigger pore size, and vice versa for DS50 GelMA.